Taxonomic novelties resulting from recent reclassification of the Lophoziaceae/Scapaniaceae clade - Söderström, Lars; de Roo, Ryan; Hedderson, Terry (Phytotaxa, 2013)
A new family, Anastrophyllaceae, is segregated from Lophoziaceae, two new genera, Neoorthocaulis and Oleolophozia are described and the following new combinations are made: Neoorthocaulis attenuatus, N. binsteadii, N. floerkei, N. hyperboreus, Barbilophozia subgen. Sudeticae, Barbilophozia sudetica and Oleolophozia perssonii.